Perlindungan Konsumen Pengguna Jasa Parkir Atas Pelepasan Tanggung Jawab Pelaku Usaha Parkir Menerapkan Klausula Baku dalam Mencapai Keadilan Berkontrak - Ida Ayu Anggita Pradnyandari; Ni Luh Made Mahendrawati; Putu Ayu Sriasih Wesna (Jurnal Preferensi Hukum, 2024)
The Consumer Protection Act 0.8 of 1999 contains provisions regarding the rights and obligations that consumers and business actors have. For example, consumers who have not received legal justice in standard agreements that create business actors, seeing the phenomenon that occurs, namely agreements made by parking business actors for consumers who use parking services, basically to meet the needs of a significant number of consumers, to make it easier for parking business actors, agreements that made for consumers who use parking services to be printed in bulk in the form of standard clauses contained in parking tickets that are made unilaterally. However, this authority contains the potential for fraud for parking business actors through the existence of a clause that is not permitted. The contents of this clause are based on the UUPK which is a clause that contains the loading of the responsibility of the businessperson for the consumer which is contained under Article 18 paragraph 1. From this it can be said that there are still many parking business actors who, in stipulating standard clause agreements in the form of parking tickets, violate the provisions of the Protection Act. Consumers are related to the discrepancy of the clause in UUPK to obtain contractual justice for consumers. With the existence of an agreement that uses the standard clause it is not allowed so that the legal consequences according to the explanation of Article 18 paragraph 3 UUPK are null and void.